The Analysis of House Prices and the Stance of Monetary Policy in the Republic of Kazakhstan - Kondybayeva, S; Ishuova, Zh (Farabi Journal of Social Sciences, 2016)
The work estimates the influence of monetary policy on actual growth of prices per square meter of housing in the Republic of Kazakhstan, using a data set comprising 76 quarters for the period from 1994:01 to 2012:04. Most aspects of the research are defined from statistical data on the economy of the Republic of Kazakhstan. The increment rate of the CPI ratio, the index of actual effective exchange rate for a group of CIS and non-CIS countries (24 countries), the average monthly rated salary per one employee, the М3 money supply, and rated house prices (1st, 2nd, 3rd , 4th class of comfort) have been calculated. A comparative analysis of the consequences of monetary policy options for the Republic of Kazakhstan with data for the Russian Federation and Republic of Belarus, shows that monetary policy in the Republic of Kazakhstan meets the standards of the leading countries.